ANALISIS LITERASI KEUANGAN DAN LINGKUNGAN MELALUI PEMBELAJARAN BERBASIS WEB TERHADAP PERILAKU KONSUMSI MAHASISWA - Dian Permana Putri; Aan Anisah; Yopi Nisa Febianti; Yuniningsih Yuniningsih (PROMOSI: Jurnal Program Studi Pendidikan Ekonomi, 2019)
One of the roles of education in the digital era, where all information can be obtained easily through existing facilities on smartphones / androids owned by students, then in an effort to improve financial literacy and student environment is expected to be achieved through web-based learning with the subject matter of scarcity theory and theory of consumer behavior. Specific research objectives, namely to produce learning media that are developed based on a valid, practical, and effective.The research method used in this research is research and development (R&D). The results of the study note that, the validity test of teaching materials was developed and carried out by three validators, the results showed that this web-based economic teaching material was valid.Assessment based on respondents' opinions on web-based teaching materials shows a positive response. The results of practicality tests on 20 students have been considered practical. In addition, the effectiveness test shows that, web-based teaching materials have good effectiveness.The conclusion is that web-based teaching materials are valid, practical, and effective, so that they can be used in the learning process in the classroom to improve the competencies students must master, namely financial literacy and environmental literacy in terms of student consumption behavior. Keywords: financial literacy, environmental literacy, web-based learning media, student consumption behavior.